11β-Hydroxysteroid dehydrogenase type 1 inhibition in idiopathic intracranial hypertension: a double-blind randomized controlled trial. Issue 1 (10th January 2020) - Markey, Keira; Mitchell, James; Botfield, Hannah; Ottridge, Ryan S; Matthews, Tim; Krishnan, Anita; Woolley, Rebecca; Westgate, Connar; Yiangou, Andreas; Alimajstorovic, Zerin; Shah, Pushkar; Rick, Caroline; et al.
Abstract: Treatment options for idiopathic intracranial hypertension are limited. The enzyme 11β-hydroxysteroid dehydrogenase type 1 has been implicated in regulating cerebrospinal fluid secretion, and its activity is associated with alterations in intracranial pressure in idiopathic intracranial hypertension. We assessed therapeutic efficacy, safety and tolerability and investigated indicators of in vivo efficacy of the 11β-hydroxysteroid dehydrogenase type 1 inhibitor AZD4017 compared with placebo in idiopathic intracranial hypertension. A multicenter, UK, 16-week phase II randomized, double-blind, placebo-controlled trial of 12-week treatment with AZD4017 or placebo was conducted. Women aged 18–55 years with active idiopathic intracranial hypertension (>25 cmH2 O lumbar puncture opening pressure and active papilledema) were included. Participants received 400 mg of oral AZD4017 twice daily compared with matching placebo over 12 weeks. The outcome measures were initial efficacy, safety and tolerability. The primary clinical outcome was lumbar puncture opening pressure at 12 weeks analysed by intention-to-treat. Secondary clinical outcomes were symptoms, visual function, papilledema, headache and anthropometric measures. In vivo efficacy was evaluated in the central nervous system and systemically. A total of 31 subjects [mean age 31.2 (SD = 6.9) years and body mass index 39.2 (SD = 12.6) kg/m 2 ] were randomized to AZD4017 ( n = 17) or placebo ( n = 14). At 12 weeks, lumbar puncture pressure was lower in the AZD4017 group (29.7 cmH2 O) compared with placebo (31.3 cmH2 O), but the difference between groups was not statistically significant (mean difference: −2.8, 95% confidence interval: −7.1 to 1.5; P = 0.2). An exploratory analysis assessing mean change in lumbar puncture pressure within each group found a significant decrease in the AZD4017 group [mean change: −4.3 cmH2 O (SD = 5.7); P = 0.009] but not in the placebo group [mean change: −0.3 cmH2 O (SD = 5.9); P = 0.8]. AZD4017 was safe, with no withdrawals related to adverse effects. Nine transient drug-related adverse events were reported. One serious adverse event occurred in the placebo group (deterioration requiring shunt surgery). In vivo biomarkers of 11β-hydroxysteroid dehydrogenase type 1 activity (urinary glucocorticoid metabolites, hepatic prednisolone generation, serum and cerebrospinal fluid cortisol:cortisone ratios) demonstrated significant enzyme inhibition with the reduction in serum cortisol:cortisone ratio correlating significantly with reduction in lumbar puncture pressure ( P = 0.005, R = 0.70). This is the first phase II randomized controlled trial in idiopathic intracranial hypertension evaluating a novel therapeutic target. AZD4017 was safe and well tolerated and inhibited 11β-hydroxysteroid dehydrogenase type 1 activity in vivo . Reduction in serum cortisol:cortisone correlated with decreased intracranial pressure. Possible clinical benefits were noted in this small cohort. A longer, larger study would now be of interest. Abstract : Preclinical research highlighted the role of 11β-hydroxysteroid dehydrogenase type 1 inhibition in modulating intracranial pressure. We report the first phase II randomized clinical trial in idiopathic intracranial hypertension evaluating safety, tolerability, in vivo efficacy and initial clinical efficacy of a novel inhibitor of 11β-hydroxysteroid dehydrogenase type 1 to lower intracranial pressure in active idiopathic intracranial hypertension. Graphical Abstract: